Exploring Therapeutic Horizons: A Bibliometric Analysis of the Use of Virtual Reality in the Treatment of Schizophrenia - Díaz, Félix (2023)
The present study explores the application of virtual reality (VR) as an innovative therapy in treating schizophrenia, a condition that presents significant challenges with existing therapeutic approaches. Through a comprehensive bibliometric review using Web of Science, Scopus, and the Bibliometrix package, this work analyzes 252 articles, highlighting the growing prominence of VR in research. The results indicate growing international collaboration, with the UK, US, and Canada leading in contributions. Keyword analysis underscores a focus on “virtual reality exposure therapy,” suggesting growing interest in this modality. The findings support the potential of VR to improve the quality of life of patients, alleviating symptoms and improving social and cognitive functions. This analysis highlights the need for more research to optimize and validate VR as a therapeutic tool, pointing towards a promising future in the personalized treatment of schizophrenia